A review on the effect of animal diets and presence of selected natural antioxidants on lipid oxidation of meat. - Bakar, Jamilah; A., Mohamed; Abbas, Kassim Ali; Abdul Rahman, Russly; Karim, Roselina (WFL Publisher, 2009)
The objective of this review paper was to collect information in scattered published works about the effect of adding natural antioxidants to the meat on decreasing the oxidative reaction and keeping quality of the meat from different animal species. The effects of animal diet, natural antioxidants, β-carotene, α-tocopherol, rosemary extract, taurine and carnosine on delaying lipid oxidation process were summarized. The outcome showed that natural antioxidants had great positive effect in delaying the lipid oxidation of the muscles of different animal species and extending the storage life of fresh meat as well as its products.